Model village: A novel approach towards inclusive development - Sahu, Raghubar; Sohane, R. K.; Kumar, Brajendu; Kumar, Rakesh (Indian Farming, 2025)
The agricultural sector ensures nation's nutritional security and livelihood of two-thirds of Indian population. Therefore, an assortment of interventions have been carried out by both government and non-government agencies with the aim of developing the farming communities. Krishi Vigyan Kendras (KVKs) and other research institutes in the Indian Council of Agricultural Research systemadopt villages with the goal of transferring new technologies, agricultural innovations and other research findings and ultimately, creating model villages that other villages can follow by successful demonstration findings. Also, infrastructure, economics, social issues and the environment were all inter-connected, they also developed in addition to farming. All the technological interventionsof agriculture and allied were included in a particular village for demonstration by Krishi Vigyan Kendras and other governmental agencies, hence it is also called a technology village.